Pengaruh Konsep Diri Terhadap Kinerja Kepala Madrasah - Neti Hasanah; Kun Nurachadijat; Sri Widaningsih (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
elf-concept is an individual's perception and assessment of himself. The purpose of this study is to understand in depth the influence of self-concept on the performance of the Principal of Madrasah Aliyah Alif Al-Ittifaq. A strong self-concept allows the Principal of Madrasah Aliyah Alif al-Ittifaq to recognize and understand self-concept from the physical self, self-concept as a process, social self-concept and self-concept related to self-image. To investigate the effect of self-concept on the performance of Madrasah principals, this study uses a qualitative approach. The research method used was a case study using in-depth interviews with the Head of Madrasah Aliyah Alif Al-Ittifaq, direct observation and document analysis as data collection techniques, source and method triangulation was used to test the authenticity of the data obtained. The results of this study reveal that self-concept is one of the factors that influence the performance of the Alif Al-Ittifaq Madrasah Aliyah Principal. A good self-concept will increase the effectiveness of the Madrasa Principal's performance. Principals who have a good self-concept tend to have better performance by knowing their own potential, strengths and weaknesses. Other factors that influence self-concept on the performance of Madrasah principals are support from staff and teachers, a positive work environment, recognition for achievements, and opportunities for professional development will provide motivation and assist in developing better leadership skills. The conclusion is that a strong and positive self-concept has a significant influence on the performance of the Madrasah Principal. For this reason, Madrasah Principals are required to develop a positive self-concept through self-development programs, leadership training, and support from all parties involved. By strengthening self-concept, Madrasah Principals can improve their performance in effectively leading and managing Madrasah Aliyah, motivating staff and teachers, and creating a conducive learning environment for students.